Carbon isotope discrimination and yield of upland rice as affected by drought at flowering - Pinheiro, Beatriz da Silveira; Austin, Roger Brian; Carmo, Maria Pereira do; Hall, Michael Alan (Pesquisa Agropecuaria Brasileira, 2000)
Field experiments involving upland rice genotypes, sown in various dates in late season, were carried out to assess the relationship of carbon isotope discrimination with grain yield and drought resistance. In each one of the three years, one trial was kept under good water availability, while other suffered water shortage for a period of 18-23 days, encompassing panicle emergence and flowering. Drought stress reduced carbon isotope discrimination measured on soluble sugars (Δs) extracted from stem uppermost internode at the end of the imposition period, but had relatively less effect on bulk dry matter of leaves, sampled at the same period, or that of uppermost internodes and grains, sampled at harvest. The drought-induced reduction in Δs was accompanied of reduced spikelet fertility and grain yield. In the three trials subjected to drought, genotypes with the highest yield and spikelet fertility had the lowest Δs. However, this relationship was weak and it was concluded that Δs is not a sufficiently reliable indicator of rice drought resistance to be useful as a screening test in breeding programs. On the other hand, grain yield and spikelet fertility of genotypes which were the soonest to reach 50% flowering within the drought imposition period, were the least adversely affected by drought. Then, timing of drought in relation to panicle emergence and to flowering appeared to be a more important cause of yield variation among genotypes than variation in Δs.
Keywords: Oryza sativa; internodes; spikelets fertility